Teacher Transition into Innovative Learning Environments A Global Perspective - Imms, Wesley (Springer Nature, 2021)
This open access book focuses on how the design and use of innovative learning environments can evolve as teaching practices and education policies change. It addresses how these new environments are used, how teachers are adapting their practices, the challenges that these changes pose, and the effective evaluation of these changes. The book reports on emerging research in learning environments, with a particular emphasis on how teachers are transitioning from traditional classrooms to innovative learning environments. It offers a significant evidence-based global assessment of current research in this field by designers, architects, educators and policy makers. It presents twenty-five cutting-edge projects from researchers in fifteen countries. Thanks to the book's comprehensive international perspective, which combines theory and practice in a single publication, readers will gain a wealth of new insights. ; This open access book focuses on the design of learning environments that change as teaching practices and education policies change. It addresses how these new environments are used, how teachers are adapting their practices, the challenges these changes present and effective evaluation of these changes. The book reports on emerging research in learning environment developments, with a particular emphasis on how teachers are transitioning from traditional classrooms to innovative learning environments and assesses the effectiveness of these learning environments. This book is the first ever evidence-based global assessment of current research in this field. Readers will gain new insight through its comprehensive international perspective that brings practice and theory together in one publication.